Effect of transdermal drug delivery therapy on anxiety symptoms in schizophrenic patients - Zhu, Cuifang; Wang, Xin-Yue; Zhao, Jing; Long, Bin; Xiao, Xudong; Pan, Ling-Yi; Yuan, Ti-Fei; Chen, Jian-Hua (Frontiers in Neuroscience, 2023)
Objective To evaluate the efficacy and safety of transdermal drug delivery therapy for schizophrenia with anxiety symptoms. Methods A total of 80 schizophrenic patients (34 males and 56 females) with comorbid anxiety disorders were randomly assigned to the treatment group (n = 40) and the control group (n = 40) with 6 weeks of follow-up. The patients in the treatment group received the standard antipsychotic drug treatment along with transdermal drug delivery therapy. The evaluation of the patients included the Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale (HAMD-17), and treatment emergent symptom scale (TESS) at baseline, 3 weeks, and 6 weeks after transdermal drug delivery therapy. The Positive and Negative Symptom Scale (PANSS) was assessed at baseline and after 6 weeks of treatment. Results After 3 and 6 weeks of treatment, the HAMA scale scores in the treatment group were lower than those in the control group (p < 0.001). However, there were no significant differences in the HAMD-17 scale scores, PANSS total scores, and subscale scores between the two groups (p > 0.05). Additionally, no significant differences in adverse effects were observed between the two groups during the intervention period (p > 0.05). After 6 weeks of penetration therapy, there was a low negative correlation between total disease duration and the change in HAMA scale score (pretreatment-posttreatment) in the treatment group. Conclusion Combined traditional Chinese medicine directed penetration therapy can improve the anxiety symptoms of patients with schizophrenia and has a safe profile.